Hubungan belanja daerah, PMDN, PMA, tenaga kerja dan pertumbuhan ekonomi Provinsi Jambi (Pendekatan Kausalitas Granger) - Maskur Latif; Syaparuddin Syaparuddin; Erni Achmad (Konsentrasi Pembangunan Regional dan Publik, Prodi Ekonomi Pembangunan, Fakultas Ekonomi dan Bisnis, Universitas Jambi, 2017)
This study aims to analyze the relationship between regional expenditure, foreign investment, domestic investment and labor towards economic growth in Jambi Province. The data used is secondary data time series period 2000 - 2015. Analysis using the Grangger Causality test method. The results of the study found that: 1) economic growth that has a two-way causality relationship to the expenditure of the capital expenditure of the Government of Jambi Province. Both variables have a causality relationship within a period of 3 years while in the period of 1 to 2 years both variables do not influence each other. 2) domestic investment that has a one-way causality relationship to economic growth Increased domestic investment is able to drive the economic growth rate of Jambi Province in a period of 2 to 3 years but on the contrary the rate of economic growth is not able to influence domestic investment both in term short and long term; 3) Foreign investment that has a one-way causality relationship to economic growth in the first and third years respectively. This means that the rate of economic growth affects the total revenue from foreign investment in the first year and foreign investment affects the economic growth rate of Jambi Province in the third year; 4) Economic growth does not have a causal relationship with labor in this study